Project-based Learning Model for strengthening Elementary students' creativity in Sciences - Musa, Muhammad Maskur; Kamal, Rahmat (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
The aim of this research is to explain PjBL: a learning model for instilling MI students' creative attitudes in science subjects. The type of research uses field studies or field research with a descriptive-qualitative approach. Data collection techniques use observation, interviews, and documentation, which are then analyzed using data reduction techniques, data presentation, and drawing conclusions. The results of the research explain that the implementation of PjBL in science subjects in class 4 consists of three stages, including the planning stage and the implementation stage, which includes: 1) Providing basic questions; 2) creating a project design; 3) preparing an activity schedule; 4) project implementation and monitoring; 5) assessment of project results; 6) evaluation of learning experience. And the evaluation stage. The embedded creativity attitudes include: 1) students' imaginations emerge when creating projects; 2) the greater the students' curiosity; 3) dare to take risks; 4) being easy to adapt to the surrounding environment; 5) increasing student independence; and 6) instilling patience and tenacity in students. Supporting and inhibiting factors that influence the implementation of PjBL come from the school, students, and parents.